Perancangan Media Pembelajaran TIK Kelas XI Berbasis Multimedia di MAS Asy-Syarif Kotolaweh - Fikhri, Miftahul; Okra, Riri; Musril, Hari Antoni; Khairuddin, Khairuddin (Indonesian Research Journal on Education, 2022)
At this time technology is developing very rapidly, this is evidenced by the ease in accessing various information at this time, and is supported by quality resources. The development of thistechnology, has had a good impact on the field of education. To achieve educational goals, students must go through the learning process. To achieve and create a classroom atmosphere that attracts students' interest in learning, the teacher must take advantage of various aspects, for example learning media. Research on designing multimedia-based ICT learning media for class XIat Mas Asy-Syarif Kotolaweh uses the 4D version of the Research and Development (R&D) method, namely Define, Design, Develop, and Disseminate. Luther Sutopo's Life Cycle development model development model, namely, Concept, Design, Material Collection, Assembly, Testing, and Distribution. The product test used in this research is the validity test, practicality test, and effectiveness test. The results of the product test that the author conducted obtained a validity test from 4 experts who obtained a value of 0.85 with a valid category, the practicality test of 2 practitioners obtained a value of 1.0 with a very high category, and the effectiveness test of 17assessors obtained a value of 0, 77 with effective category.